Dissolution kinetics of iron-, manganese-, and copper-containing synthetic hydroxyapatites - Sutter, B (Soil Science Society of America journal. Soil Science Society of America, 2005)
Micronutrient-substituted synthetic hydroxyapatite (SHA) is being evaluated by the National Aeronautics and Space Administration's (NASA) Advanced Life Support (ALS) Program for crop production on long-duration human missions to the International Space Station or for future Lunar or Martian outposts. The stirred-flow technique was utilized to characterize Ca, P, Fe, Mn, and Cu release characteristics from Fe-, Mn-, and Cu-containing SHA in deionized (DI) water, citric acid, and diethylene-triamine-pentaacetic acid (DTPA). Initially, Ca and P release rates decreased rapidly with time and were controlled by a non-SHA calcium phosphate phase(s) with low Ca/P solution molar ratios (0.91-1.51) relative to solid SHA ratios (1.56-1.64). At later times, Ca/P solution molar ratios (1.47-1.79) were near solid SHA ratios and release rates decreased slowly indicating that SHA controlled Ca and P release. Substituted SHA materials had faster dissolution rates relative to unsubstituted SHA. The initial metal release rate order was Mn >> Cu > Fe which followed metal-oxide/phosphate solubility suggesting that poorly crystalline metal-oxides/phosphates were dominating metal release. Similar metal release rates for all substituted SHA (approximately 0.01 cmol kg-1 min-1) at the end of the DTPA experiment indicated that SHA dissolution was supplying the metals into solution and that poorly crystalline metal-oxide/phosphates were not controlling metal release. Results indicate that non-SHA Ca-phosphate phases and poorly crystalline metal-oxide/phosphates will contribute Ca, P, and metals. After these phases have dissolved, substituted SHA will be the source of Ca, P, and metals for plants